THE CORRELATION BETWEEN SUSTAINABLE VALUE ADDED AND FINANCIAL PERFORMANCE AMONG INDONESIAN LISTED COMPANIES - Tedjobuwono, Robertus (Accounting Department, 2017)
Sustainability awareness is growing very fast in the society and companies. A lotof companies do Corporate Social Responsibility (CSR) to satisfy stakeholders,while in return they expect to get a better performance. This research discusses the correlation of sustainability performance to financial performance, by usingsustainable value added as a mean of measurement. This measurement monetize the impact of environmental and society performance, so the performance can be measured precisely. This research uses Spearman Correlation to analyze the correlation of thirty-four samples. From this research, it is found that there is correlation between CSR and financial performance